Achieving Minimum Clinically Important Difference in Oxford Knee Score and Short Form-36 Physical Component Summary Is Less Likely with Single-Radius Compared with Multiradius Total Knee Arthroplasty in Asians - Lee, Wu Chean; Bin Abd Razak, Hamid Rahmatullah; Allen, John Carson; Chong, Hwei Chi; Tan, Hwee Chye Andrew (The Journal of Knee Surgery, 2019)
Single-radius (SR) and multiradius (MR) total knee arthroplasties (TKAs) have produced similar outcomes, albeit most studies originate from Western nations. There are known knee kinematic differences between Western and Asian patients after TKA. The aim of this study is to compare the short-term patient-reported outcome measures (PROMs) of SR-TKA versus MR-TKA in Asians. Registry data of 133 SR-TKA versus 363 MR-TKA by a single surgeon were analyzed. Preoperative and 2-year postoperative range of motion (ROM) and PROMs were compared with Student's t-test and Mann–Whitney U-test. Logistic regression model was used to evaluate the odds of SR-TKA or MR-TKA achieving the minimum clinically important difference (MCID) of studied outcomes. Patients in both groups had similar age (65.7 ± 7.6 vs. 65.8 ± 8.2 years; p = 0.317), gender proportion (71% females vs. 79% females; p = 0.119), and ethnic distribution (80% Chinese vs. 84% Chinese; p = 0.258). Preoperatively, there were no statistically significant differences between both groups for ROM, Knee Society Score (KSS), Oxford Knee Score (OKS), and Short Form (SF)-36 scores. At 2 years, all outcomes were statistically similar or failed to achieve a difference of MCID. Controlling for all preoperative variables, SR-TKA has significantly lower odds of achieving MCID for OKS (odds ratio [OR]: 0.275, 95% confidence interval [CI]: 0.114–0.663; p = 0.004) and SF-36 Physical Component Summary (PCS) (OR: 0.547; 95% CI: 0.316–0.946; p = 0.031) compared with MR-TKA. In conclusion, there are no significant differences in the absolute PROMs between SR-TKA and MR-TKA at 2 years following TKA in Asians. However, SR-TKA has significantly lower odds of achieving the MCID for OKS and SF-36 PCS.
Keywords: total knee arthroplasty; single radius; multiradius; Asians; minimum clinically important difference